Synthesis of 11C‐labeled Sulfonyl Carbamates through a Multicomponent Reaction Employing Sulfonyl Azides, Alcohols, and [11C]CO. Issue 6 (5th October 2016) - Stevens, Marc Y.; Chow, Shiao Y.; Estrada, Sergio; Eriksson, Jonas; Asplund, Veronika; Orlova, Anna; Mitran, Bogdan; Antoni, Gunnar; Larhed, Mats; Åberg, Ola; Odell, Luke R.
Abstract: We describe the development of a new methodology focusing on 11 C‐labeling of sulfonyl carbamates in a multicomponent reaction comprised of a sulfonyl azide, an alkyl alcohol, and [ 11 C]CO. A number of 11 C‐labeled sulfonyl carbamates were synthesized and isolated, and the developed methodology was then applied in the preparation of a biologically active molecule. The target compound was obtained in 24±10 % isolated radiochemical yield and was evaluated for binding properties in a tumor cell assay; in vivo biodistribution and imaging studies were also performed. This represents the first successful radiolabeling of a non‐peptide angiotensin II receptor subtype 2 agonist, C21, currently in clinical trials for the treatment of idiopathic pulmonary fibrosis. Abstract : F‐Ang‐tasti‐ 11 C ! A new multicomponent method of preparation of 11 C‐labeled sulfonyl carbamates from sulfonyl azides, alcohols, and [ 11 C]CO is described. The method can be used to label a series of substrates, including a non‐peptide angiotensin II receptor subtype 2 agonist currently in clinical trials. This compound is evaluated in a cell‐based prostate cancer assay, and biodistribution and positron emission tomography imaging studies are conducted in healthy rats.